Linux for non-geeks : a hands-on, project-based, take-it-slow guidebook - Grant, Rickford (No Starch Press, 2004)
A plain-English, highly accessible guide to Linux for anyone. Readers will find coverage of installation, using the desktops, going online, customization, printing, installing programs, the Linux terminal and command line, compiling programs from source code, accessing Windows partitions and USB devices, playing audio, adding fonts, Wi-Fi, and troubleshooting. Based on Red Hat's Fedora Core.